2023
DOI: 10.1097/md.0000000000033534
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional activities of brain in patients with vascular cognitive impairment: A case-controlled magnetic resonance imaging study

Abstract: This study aimed to identify abnormal brain regions and imaging indices of vascular cognitive impairment (VCI) and explore specific imaging diagnostic markers of VCI. In this study, 24 patients with VCI were allocated to the VCI group and 25 healthy subjects were assigned to the healthy control (HC) group. Demographic data and neuropsychological test scores were compared using SPSS 25.0. The structural and functional imaging data were post-processed and statistically analyzed using CAT12, DPARSF and SPM12 soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Accordingly, excision of the frontal rectus gyrus, which was previously assumed to not impair limb movement or sensory function, is highly susceptible to cognitive problems. Previous research revealed decreased REC grey volume and elevated ReHo rectus gyrus, supporting the role of REC in cognitive function in patients with vascular cognitive impairment [15] or acute ischemic stroke [23]. Due to the subjects' inclusion conditions and comparisons with a healthy control group, their outcomes may differ from ours.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Accordingly, excision of the frontal rectus gyrus, which was previously assumed to not impair limb movement or sensory function, is highly susceptible to cognitive problems. Previous research revealed decreased REC grey volume and elevated ReHo rectus gyrus, supporting the role of REC in cognitive function in patients with vascular cognitive impairment [15] or acute ischemic stroke [23]. Due to the subjects' inclusion conditions and comparisons with a healthy control group, their outcomes may differ from ours.…”
Section: Discussionsupporting
confidence: 47%
“…Multimodal functional imaging including voxel-based morphometric analysis found signi cant grey matter volume reductions in MTG in VaMCI patients [51]. VCI also observed dramatically changed ReHo or ALFF in MTG [15,52]. The whole-brain function network has altered FC pattern and density in MTG, according to fMRI [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation